2021
DOI: 10.21873/invivo.12488
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Treatment of an Advanced Prostate-cancer Patient With Oral Methioninase Resulted in Long-term Stabilization of Rapidly Rising PSA Levels

Abstract: Background/Aim: Advanced prostate cancer is a recalcitrant disease with very limited treatment options. Our laboratory discovered methionine addiction, presumably a characteristic of all cancer types, including prostate cancer, which can be targeted by methionine restriction (MR), through treatment with oral recombinant methioninase (o-rMETase). Patients and Methods: o-rMETase was produced by fermentation of recombinant E. coli containing the Pseudomonas putida methioninase gene, and purified by column chromat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 8 publications
0
19
0
Order By: Relevance
“…rMETase alone or at combination with chemotherapy has been shown to be active clinically with major cancer types (20)(21)(22)(23)(24). Synergy of methionine restriction and chemotherapy was discovered by our team (25) and is called the Hoffman protocol, which targets methionine addiction which is the fundamental chracteristic of cancer (13,(26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
“…rMETase alone or at combination with chemotherapy has been shown to be active clinically with major cancer types (20)(21)(22)(23)(24). Synergy of methionine restriction and chemotherapy was discovered by our team (25) and is called the Hoffman protocol, which targets methionine addiction which is the fundamental chracteristic of cancer (13,(26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
“…Previously we have shown that o-rMETase has potential clinical efficacy in prostate and pancreatic cancer patients (30)(31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
“…o-rMETase has shown clinical promise as therapy for advanced prostate cancer, stage IV pancreatic cancer and rectal cancer (25)(26)(27)(28)(29). Future studies will determine efficacy of rMETase in clinical breast cancer.…”
Section: Discussionmentioning
confidence: 99%